2022
DOI: 10.3390/tropicalmed7080155
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mutations in the Pfdhfr, Pfdhps, and Pfmdr1 Genes of Malarial Parasites Isolated from Symptomatic Patients in Dogondoutchi, Niger

Abstract: The effectiveness of artemisinin-based combination therapies (ACTs) depends not only on that of artemisinin but also on that of partner molecules. This study aims to evaluate the prevalence of mutations in the Pfdhfr, Pfdhps, and Pfmdr1 genes from isolates collected during a clinical study. Plasmodium genomic DNA samples extracted from symptomatic malaria patients from Dogondoutchi, Niger, were sequenced by the Sanger method to determine mutations in the Pfdhfr (codons 51, 59, 108, and 164), Pfdhps (codons 436… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 38 publications
6
6
1
Order By: Relevance
“…The 436A mutation has been described throughout Africa at varying levels of frequency (41)(42)(43)(44). Detecting the I431V mutation in this study, albeit at a low prevalence, con rms a previous nding from Ghana and Niger, two countries neighboring Burkina Faso (41)(42)(43)(44). The impact of the I431V mutation on the continued use of SP for IPTp remains to be elucidated (45).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The 436A mutation has been described throughout Africa at varying levels of frequency (41)(42)(43)(44). Detecting the I431V mutation in this study, albeit at a low prevalence, con rms a previous nding from Ghana and Niger, two countries neighboring Burkina Faso (41)(42)(43)(44). The impact of the I431V mutation on the continued use of SP for IPTp remains to be elucidated (45).…”
Section: Discussionsupporting
confidence: 79%
“…The mutation A437G was not found as well in the study conducted in Niger on symptomatic malaria cases in pre-treatment (41). The 436A mutation has been described throughout Africa at varying levels of frequency (41)(42)(43)(44). Detecting the I431V mutation in this study, albeit at a low prevalence, con rms a previous nding from Ghana and Niger, two countries neighboring Burkina Faso (41)(42)(43)(44).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The PCR/Sequencing method for pfk13, pfdhfr, pfdhps, pfcrt and pfmdr genes was used to study molecular resistance to anti-malarials [ 14 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…In 2017, a study of pfdhfr and pfdhps markers associated with SP resistance showed 97.4% prevalence for pfdhfrS108N , 92.6% for PfdhfrC59R and 85.0% for PfdhfrN51I in [ 14 ]. A 2018 study showed a prevalence of 59.0% for PfdhpsA437G and 43.1% for PfdhpsS436A [ 15 ].…”
Section: Introductionmentioning
confidence: 99%